Hunting Adeline - Carlton, H. D. (Place of publication not identified H. D. Carlton, 2022)
"The Diamond: Death walks alongside me, but the reaper is no match for me. I'm trapped in a world full of monsters dressed as men, and those who aren't as they seem. They won't keep me forever. I no longer recognize the person I've become, And I'm fighting to find my way back to the beast who hunts me in the night. They call me a diamond, But they've only created an angel of death. The Hunter: I was born a predator, With ruthlessness ingrained in my bones. When what's mine is stolen from me in the night, like a diamond hidden within a fortress, I find that I can no longer contain the beast. Blood will paint the ground as I tear apart this world to find her. And bring her back to where she belongs. No one will escape my wrath, especially not those who have betrayed me"--Amazon.com.
"This book contains very dark triggering situations such as graphic rape (these scenes are detailed, so please proceed with caution.) There is also graphic violene and gore, torture, sexual assault, kidnapping, psychological abuse, physical abuse, mental abuse, explicit sexual situations, human trafficking, slave trade, grooming, severe PTSD, and very particular kinks such as blood play, knife play, degradation, and somnophhilia." -- Important note
113176
Keywords: Man-woman relationships -- Fiction; Violence -- Fiction; Torture -- Fiction; Child trafficking -- Fiction; Human trafficking -- Fiction; Rape -- Fiction; Kidnapping -- Fiction; Stalkers -- Fiction; Violence -- Romans, nouvelles, etc; Torture; Thrillers (Fiction); Horror fiction; Fiction; Romance fiction; Erotic fiction